Association between Helicobacter pylori Infection and Occurrence of Anemia among Pregnant Women Attending Antenatal Care in Kulito Health Center, Halaba Zone, South Ethiopia, 2018. (24th July 2020) - Abdella, Bahredin; Ibrahim, Mohammed; Tadesse, Iyasu; Hassen, Kalkidan; Tesfa, Mekonnin
Abstract : Background . Anemia in pregnancy is defined as a hemoglobin (Hb) concentration of less than 11 grams (gm)/deciliter (dl) in venous blood. Globally, it affects 1.62 billion people. In developing countries, anemia is a major cause of maternal and child morbidity and mortality. Globally, anemia contributes to 20% of all maternal deaths. Nearly 50% of the world's population is estimated to be infected with Helicobacter pylori (HP). High prevalence of HP among pregnant women was also reported in developing countries than developed ones. The association between HP infection and occurrence of anemia is not well known in Ethiopia. Therefore, the aim of this study was to determine the association between anemia and Helicobacter pylori infection among pregnant women attending antenatal care follow-up in Kulito Health Center, Halaba Zone, South Ethiopia. Methods . Institution-based cross-sectional study was employed. Systematic random sampling procedure was employed to select 236 pregnant women who attended antenatal care at Kulito Health Center. An interviewer-administered questionnaire supplemented by laboratory tests was used to obtain the data. The collected data were analyzed by using SPSS version 20.0. Results . The prevalence of anemia among antenatal care attendant pregnant women of Kulito Health Center was 27.5% with 36 (15.2%) of mild, 29 (12.3%) of moderate, and no severe cases of anemia. The overall prevalence of HP infection among study participants was found to be 129 (54.7%) (95% CI: 47.9–61.4). Factors significantly associated with anemia were presence of HP infection (AOR = 3.064, 95% CI: 1.336 7.027), low interpregnancy gap (AOR = 2.863, 95% CI: 1.245–6.582), being on the third trimester (AOR = 6.457; 95% CI: 1.276–32.729), and mid-upper arm circumference (MUAC) level < 21 cm (AOR = 2.595, 95% CI: 1.044–6.450). Conclusion . This study revealed that anemia and HP infection were highly prevalent among pregnant women attending the antenatal follow-up clinic in Kulito Health Center. HP infection, low interpregnancy gap, being on the third trimester, and MUAC less than 21 cm were the independent factors associated with anemia. Recommendation . Pregnant women should be aware that anemia is a problem that can be prevented by early prevention and treatment of HP infection and undernutrition, using family planning to widen the interpregnancy gap. Further experimental studies are warranted to determine the cause and effect of the association between anemia and HP infection.